Risk factors and characteristics of cervical cancer patients under 40 years old at Prof Dr I.G.N.G. Ngoerah Hospital Denpasar, Bali from January until December 2022 - I Nyoman Gede Budiana; I Nyoman Bayu Mahendra; I Gde Sastra Winata; Kade Yudi Saspriyana; Kevin Agastya Duarsa; Pande Made Suwanpramana; Rayvany Uil; Dewi, Putu Pradnya Paramitha; Made Yudha Ganesa Wikantyas Widia; Eric Gradiyanto Ongko; I Gede Indra Kumara; Charles Richard Thene; Johan Qalaba; Made Ayu Prabawaty Indraswari; Ida Bagus Arjuna; Putu Harrista Indra Pramana; Ernest T. B. Sianturi (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2023)
Background: Cervical cancer is the main cause of death for women worldwide. 500.000 new cases and 250.000 deaths are reported each year. In Indonesia, women as young as 25 are being diagnosed with this disease. The study will be conducted at Prof.Dr.I.G.N.G Ngoerah Hospital from January to December 2022 to analyze cervical cancer patients under 40. This study aimed to see the profile and the distribution of 40 year-old women with cervical cancer at our hospital. Methods: This descriptive study was conducted using medical records that were centered around female patients who were below 40 years of age and had been diagnosed with cervical cancer in Prof.Dr.I.G.N.G Ngoerah hospital in January - December 2022. Purposive sampling was done, and the samples were selected according to the inclusion criteria. The resulting data was presented in a table format. Results: Fifty-one cervical cancer patients aged under 40 years were included, with most of the age group being 30 – 39 years (88.2%). Twenty-eight patients (54.9%) were in the two-to-three parity group. The most dominant stage of cervical cancer is stage IIIB, with a total of 20 people (39.2%). Non-keratinizing squamous cell carcinoma (NKSCC) was the most common histopathological appearance (64.7%). Conclusions: The study found that cervical cancer commonly affects those between 30-39 years old, particularly in the form of NKSCC. Many patients are diagnosed in advanced stages of the disease. Early screening, education, and vaccination programs are crucial in preventing cervical cancer.